Neo-Orientalism and Modern Persian Literature - Khorrami, Mohammad Mehdi (Iranian Journal of Translation Studies, 2006)
The process of representing works from a literary tradition in a different cultural framework through translation is not determined exclusively by the translator or the one who seems to be selecting the works to be translated. In fact, in the majority of cases, this process is greatly influenced by elements of the culture which is going to host these works. In the case of modern Persian literature and its representation in the West through translation, some of these elements which function through the market are highlighted by an approach which, under the guise of a postmodernism/postcolonialism, perpetuates the old orientalist clichés and concepts. An examination of some of the Persian literary works translated and published in anthologies during the past two decades in the United States clearly demonstrates how neo-orientalist clichés have succeeded in imposing themselves on the process of selecting which works are to be translated. These clichés are constructed based on the notion that literary works of Persian literature (and many other literary traditions of the region) are useful to the West only because they could reveal social and political issues in Iran. This notion informs and is informed by preconceived views about those social and political issues. Accordingly, therefore, specific and limited expectations about Persian literature are instituted. Such a market is further defined by another approach which assumes that Persian literary work is in an elementary stage and that thus readers can have only limited literary expectations from it. Clearly this image also influences the selection process, but the main consequence of such an approach is that it ignores the need to study the unique characteristics of the Persian literary tradition and that the translated works are then almost never subject to rigorous critical examination; and so the vicious cycle continues. Considering these obstacles which frustrate efforts to use translation as a tool to present a true image of the Persian literary tradition, I argue that the act of translation should be accompanied by a theoretical undertaking aimed at establishing concepts and structures through which works of Persian literature in translation can be explored. It is only in this context that the act of translation could lead to the presentation of true examples of the Persian literary tradition within Western cultures.